Arthroscopy and arthrotomy were equally effective for medial meniscal release but arthroscopy was minimally advantageous at preventing iatrogenic damage to the caudal cruciate ligament: a canine cadaveric study - Gale, Dana N.; Frederick, Steven W.; Hettlich, Bianca F.; Au, Jennifer J.; Motta, Tatiana (Frontiers in Veterinary Science, 2025)
ObjectiveTo compare efficacy of four techniques used for medial meniscal release by medial caudal meniscotibial ligament transection and evaluate associated iatrogenic damage to the medial meniscus, caudal cruciate ligament (CdCL), and articular cartilage of the canine stifle joint.Study designTwenty-four pairs of canine cadaveric pelvic limbs were randomly assigned to groups by methods of approach, cranial tibial translation, and meniscal release. I: arthrotomy, Hohmann, #11 scalpel blade; II: arthrotomy, Hohmann, #64 Beaver blade; III: arthroscopy, Hohmann, meniscal hook knife; IV: arthroscopy, no joint translation, meniscal hook knife. Post-procedure stifle dissection and evaluation of meniscal release success rate and presence of iatrogenic damage were performed. Fisher’s exact tests were performed for meniscal release and damage comparisons. Iatrogenic damage to the CdCL and articular cartilage were compared using generalized linear mixed effects model and linear mixed effects models (G/LMM) respectively.ResultsIncomplete meniscal release was identified in 0/12 (0%) stifles in group I, 1/12 (8.3%) stifles in group II, 2/12 (16.7%) stifles in group III, and 1/12 (8.3%) stifles in group IV (p = 0.89, Fisher’s exact test). There was no difference in iatrogenic meniscal damage rates between groups (p = 0.48, Fisher’s exact test). There were no differences in total surface area of iatrogenic articular cartilage damage in any tested region between groups: femoral trochlea (p = 0.32, LMM), femoral condyles (p = 0.54, LMM), tibia (p = 0.28, LMM). Group I had more iatrogenic damage to the CdCL than group IV (p = 0.04, GLMM); no other differences were found.ConclusionArthroscopy and arthrotomy were equally effective for performing medial meniscal release by transection of the medial caudal meniscotibial ligament. Arthroscopic evaluation and medial meniscal release without joint translation was minimally advantageous in preventing iatrogenic damage to the CdCL.